2006
DOI: 10.1089/dia.2006.8.419
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Pilot Feedback Survey of 200 Users of the AIDA Version 4 Educational Diabetes Program. 17—Quantitative Survey Data

Abstract: This column reports a detailed, questionnaire-based, post-release feedback survey of 200 users of the AIDA version 4 educational diabetes simulator. AIDA is a freeware computer program that permits the interactive simulation of plasma insulin and blood glucose profiles for educational, demonstration, self-learning, and research purposes. Since its Internet launch in 1996 over 700,000 visits have been logged to the AIDA Websites-including www.2aida.org-and over 200,000 program copies have been downloaded free-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Some good examples on simulators being an efficient library of physiological knowledge are [124]–[126]. …”
Section: Maximal Modelsmentioning
confidence: 99%
“…Some good examples on simulators being an efficient library of physiological knowledge are [124]–[126]. …”
Section: Maximal Modelsmentioning
confidence: 99%
“…Among these advisory systems, KADIS, AIDA (Diabetic Software Simulation Program), and the Diabetes Advisory System (DIAS) are the only interactive model-based systems focused on interactive simulation of insulin/glucose profiles (9,10,12). While AIDA is a freeware computer program for educational purposes (9), DIAS can be used to predict the effects of changes in insulin dose or food intake (10).…”
mentioning
confidence: 99%
“…Furthermore, upgrades to AIDA online require only one version of the program to be changed, and these changes then automatically become accessible to anyone from anywhere in the world. In addition, many users have asked for a windows-based, mouse-controlled “point and click” version of AIDA [54]. AIDA online provides just such an easy to use simulator with a standard user interface accessible in a familiar web browser format.…”
Section: Discussionmentioning
confidence: 99%
“…However, potentially one web-based server could have difficulty supporting the extent of usage which has been reported with the downloadable AIDA PC software. For instance, a detailed survey of AIDA v4 users has revealed that 16,790 simulations were run by 200 users [54]. Over a similar period—around the same time—over 16,700 downloads of the AIDA PC software were logged at the main AIDA website.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation